Pengaruh Edukasi Kesehatan dengan Flipped Classroom terhadap Peningkatan Pengetahuan tentang Penyakit Gastritis pada Siswa SMA - Hanifah, Hanifah; Suyanto; Indah Sri Wahyuningsih (Journal of Midwifery and Health Science of Sultan Agung, 2025)
Gastritis is inflammation of the gastric mucosa which often occurs among teenagers. This research is motivated by the low level of knowledge among teenagers about gastritis, which is caused by traditional learning methods that are less interactive. The flipped classroom method was chosen as an alternative learning strategy that allows students to study independently at home via digital media, before applying this knowledge in discussions and activities in class. With the flipped classroom method, it is hoped that students can be more actively involved in the learning process and increase their understanding of gastritis. This research uses a quantitative research design with a quasi-experimental research method using a two group pretest and posttest group design approach. The samples used were students from class XII IPA and XI IPS MA Darut Taqwa Semarang. The technique used was simple random sampling of 48 respondents. The statistical tests in this research are the marginal homogeneity test and the chi-square test. The results of statistical tests show that after treatment the control group and intervention group obtained a p value of 0.005<0.05, this shows that there is an influence of the learning method using the flipped classroom on increasing knowledge about gastritis.